Enhancement of electrical and electrochemical properties of sodium bromide incorporated with poly (ethylene oxide)/poly (vinylidene fluoride-hexafluoropropylene) solid blend polymer electrolytes for electrochemical double layer capacitors. (30th November 2022) - Shenbagavalli, S.; Muthuvinayagam, M.; Revathy, M.S.
Abstract: Sodium-ion conducting solid blend polymer electrolytes are prepared with Poly (ethylene oxide) (PEO)/Poly (vinylidene fluoride-hexafluoropropylene) P(VdF-HFP)/Sodium Bromide (NaBr) by solution casting technique. Different analysis such as structural, vibrational, electrical and electrochemical studies reveal promising properties of the prepared solid polymer electrolytes (SPE). The XRD analysis illustrates the increase in amorphous nature of the sample up to 8 wt% NaBr salt concentration. The complexation between polymers and salt has been examined by FTIR analysis. To examine the electrical conductivity, AC impedance analysis was performed in the temperature range of 303–373 K. The higher ionic conductivity ( σ ) of 1.10 × 10 −3  S cm −1 was found for the solid polymer electrolyte (SPE) containing 8 wt% NaBr at room temperature. The temperature dependence of ionic conductivity resembles Arrhenius behavior. The dielectric behavior has been analyzed using dielectric permittivity (ε*) and the relaxation frequency (τ) has been calculated from the loss tangent spectra (tan δ). The modulus spectra indicate the non-Debye nature of the material. Wagner's DC polarization technique was used to compute the transference number. According to the LSV analysis, the solid blend polymer electrolytes have the suitable electrochemical potential window to be used in electrochemical devices. The cyclic voltammetry (CV) and charge-discharge studies (GCD) of the assembled electrochemical double-layer capacitor (EDLC) show specific capacitance ( C sp ) values of 12.9 F/g and 10.4 F/g respectively. Further the better performance of EDLC is confirmed with its energy density (3.25 to 2.12 Wh/kg), power density (750 to 2623 W/kg) as well as coulombic efficiency (98.2 %) after 1500 cycles. Graphical abstract: Unlabelled Image Highlights: Highly Sodium ion conducting solid blend polymer electrolytes are prepared with PEO/P(VdF-HFP) by solution casting technique. The XRD, FTIR and SEM analysis confirms the complexation and functional groups present in the electrolytes. The Electrochemical double-layer capacitor(EDLC) show specific capacitance ( C sp ) values of 12.9 F/g. The better performance of EDLC is confirmed with it's energy density(3.25 to 2.12 Wh/kg), power density(750 to 2623 W/kg). The coulombic efficiency (98.2%) is confirmed even after 1500 cycles. Thus, it is confirmed that this high ionic conductivity membrane is found to be suitable for energy storage devices.